2013
DOI: 10.1128/jvi.02676-12
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Tegument Protein pUL37 Interacts with Dystonin/BPAG1 To Promote Capsid Transport on Microtubules during Egress

Abstract: bHerpes simplex virus 1 (HSV-1) is a neurotropic virus that travels long distances through cells using the microtubule network. Its 125-nm-diameter capsid is a large cargo which efficiently recruits molecular motors for movement. Upon entry, capsids reach the centrosome by minus-end-directed transport. From there, they are believed to reach the nucleus by plus-end-directed transport. Plus-end-directed transport is also important during egress, when capsids leave the nucleus to reach the site of envelopment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 48 publications
(71 reference statements)
3
76
0
Order By: Relevance
“…However, it is likely that the UL36-UL37 complex does not regulate viral secondary envelopment itself but promotes nucleocapsid transport to sites in the cytoplasm for HSV-1 secondary envelopment. This proposal is based on previous reports that: (i) cytoplasmic nucleocapsids were transported along microtubules to the sites for viral secondary envelopment (54,55), (ii) the UL36-UL37 complex appeared to be a bridge between nucleocapsids and microtubule motors (56,57), (iii) nucleocapsids of either the UL36-null or UL37-null mutant virus showed reduced ability to be transported in the cytoplasm (54,55), and (iv) nucleocapsids of a UL36-null mutant virus, a UL37-null mutant virus, or a UL36 mutant virus with the deletion of a minimal domain required for UL37 binding did not associate with cytoplasmic membranes (11,12,20). In this study, we showed that mutations in UL51 and/or UL14 accumulated not only unenveloped nucleocapsids, as observed with the mutations in UL36 or UL37 (11,12), but also partially enveloped nucleocapsids that appeared to be arrested at the membrane deformation stage during HSV-1 cytoplasmic budding.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that the UL36-UL37 complex does not regulate viral secondary envelopment itself but promotes nucleocapsid transport to sites in the cytoplasm for HSV-1 secondary envelopment. This proposal is based on previous reports that: (i) cytoplasmic nucleocapsids were transported along microtubules to the sites for viral secondary envelopment (54,55), (ii) the UL36-UL37 complex appeared to be a bridge between nucleocapsids and microtubule motors (56,57), (iii) nucleocapsids of either the UL36-null or UL37-null mutant virus showed reduced ability to be transported in the cytoplasm (54,55), and (iv) nucleocapsids of a UL36-null mutant virus, a UL37-null mutant virus, or a UL36 mutant virus with the deletion of a minimal domain required for UL37 binding did not associate with cytoplasmic membranes (11,12,20). In this study, we showed that mutations in UL51 and/or UL14 accumulated not only unenveloped nucleocapsids, as observed with the mutations in UL36 or UL37 (11,12), but also partially enveloped nucleocapsids that appeared to be arrested at the membrane deformation stage during HSV-1 cytoplasmic budding.…”
Section: Discussionmentioning
confidence: 99%
“…UL36p and UL37p can also associate with organelles in the absence of capsids, since they are assembled into L particles (enveloped structures lacking capsids) in a mutually interdependent fashion (47)(48)(49) and because UL36p can mediate capsid-independent targeting of UL37p to the TGN (50). Loss of UL37p and UL36p results in similar phenotypes: accumulation of nonenveloped capsids in the nucleus and cytosol (27,41,51,52) and a decrease in microtubule-mediated transport of capsids (39,40,42,53). The interplay between UL36p/UL37p, the ESCRT apparatus, and other virally encoded proteins during capsid-membrane association and envelopment (8,10,46,54) is not well understood.…”
mentioning
confidence: 99%
“…Interestingly, HSV-1 pUL37 has recently been shown to interact with the MT-binding protein dystonin/BPAG1 to promote capsid transport on microtubules (52). Moreover, the same group showed that dystonin silencing during entry impaired HSV-1 capsid accumulation as a ring around the nuclear periphery (53), a phenotype very similar to the one observed for the MuHV-4 ORF63 STOP mutant (Fig.…”
Section: Discussionmentioning
confidence: 68%